A community study of the effect of polycyclic aromatic hydrocarbon metabolites on heart rate variability using the Framingham score - Feng, Yingying (Occup Environ Med, 2014)
OBJECTIVES: To investigate the effects of the urinary metabolite profiles of background exposure to the atmospheric pollutants polycyclic aromatic hydrocarbons (PAHs), and Framingham risk score (FRS), which assesses an individual’s cardiovascular disease risk, on heart rate variability (HRV). METHODS: The study, conducted from April to May 2011 in Wuhan, China, included 1,978 adult residents with completed questionnaires, physical examinations, blood and urine samples, and 5-min HRV indices [including standard deviation of NN intervals (SDNN), root mean square successive difference (rMSSD), low frequency (LF), high frequency (HF) and their ratio (LF/HF), and total power (TP)] obtained from 3-channel Holter monitor. 12 urinary PAH metabolites were measured by gas chromatography–mass spectrometry. FRS was calculated based on age, sex, lipid profiles, blood pressure, diabetes, and smoking status. Linear regression models were constructed after adjusting for potential confounders. RESULTS: Elevated ΣOHNa was significantly associated, in a dose-responsive manner, with decreased SDNN and LF/HF (P(trend) = 0.014 and 0.007, respectively); elevated ΣOHFlu was significantly associated with reduced SDNN, LF, and LF/HF (P(trend) = 0.027, 0.003, and < 0.0001, respectively); and elevated ΣOH-PAHs was associated with decreased LF and LF/HF (P(trend) = 0.005 and < 0.0001, respectively). Moreover, increasing quartiles of FRS were significantly associated with decreased HRV indices, except LF/HF (P(trend) <0.001). Interestingly, individuals in low-risk subgroups had greater decreases in SDNN, LF, and LF/HF in relation to ΣOH-PAHs, ΣOHNa, and ΣOHFlu than those in high-risk subgroups (all P <0.05). CONCLUSIONS: Environmental PAHs exposure may differentially affect HRV based on individual coronary risk profiles.